P719 Does radiation to the pelvis portend worse ileal pouch outcomes? An international multi-institution collaborative study. (16th January 2018) - Lightner, A; Spinelli, A; McKenna, N; Warusavitarne, J; Fleshner, P
Abstract: Background: Little is known regarding short-term morbidity and long-term functional outcome of patients with an ileal pouch-anal anastomosis (IPAA) exposed to pelvic radiation. We herein report the largest series to date regarding the effects of pelvic radiation on (1) 30-day postoperative outcomes and (2) long-term functional outcomes following IPAA. Methods: A retrospective chart review was conducted of patients who received pelvic radiation therapy (XRT) before or after IPAA between 1980 and 2017 across three international inflammatory bowel disease centres. Outcomes among patients who received XRT prior to IPAA were compared with those who received XRT after IPAA using a Fisher exact test. Results: The study cohort of 18 patients included 9 (50%) females and had a median age of 47 (range, 20–68) years. Underlying disease diagnosis was ulcerative colitis ( n = 10), familial adenomatous polyposis ( n = 4) and hereditary nonpolyposis colorectal cancer ( n = 4). Indications for XRT were rectal adenocarcinoma ( n = 13), prostate adenocarcinoma ( n = 3), or anal squamous cell carcinoma (ASCC) ( n = 2). XRT was given prior to IPAA in 12 (67%) patients and after IPAA in 6 (33%) patients. All patients received a dose of 45–50 Gy, except one patient with prostate cancer who received 70 Gy. 30-day post-operative infectious complications were 33% (perianal abscess (2); anastomotic leak (2)) in patients who received XRT prior to IPAA vs. none in patients who received XRT after IPAA ( p = 0.25). Of the 12 patients who received XRT before IPAA, patients had a median of 4.5 daytime bowel movements, 1.5 night-time bowel movements, no daytime incontinence, and only one patient used pads at a median follow-up of 25 months (range 11–163). The one patient who received 70 Gy XRT for prostate cancer prior to IPAA developed refractory pouchitis and underwent pouch excision 15 months after IPAA. Of the 6 patients who received XRT after IPAA, 3 had rectal adenocarcinoma diagnosed at time of IPAA and received XRT within 6 months of IPAA, 2 had prostate cancer 8 years after IPAA, and one had ASCC 24 years after IPAA. All patients with rectal adenocarcinoma had systemic recurrence by 14 months and two died within 24 months. The remaining four patients reported 8 daytime bowel movements, 3.5 night-time bowel movements, 75% with daytime incontinence, and 100% with pad usage at a median follow-up of 90 months (range 25–315). Conclusions: Pelvic radiation administered prior to IPAA formation may increase 30-day infectious complications, but does not seem to worsen long-term functional outcomes. However, when pelvic radiation is given to an IPAA in situ, patients experience persistent poor pouch function that does not recover following radiation therapy.